Mass Spectrometer (MS) troubleshooting guide - Odenkirk, Melanie T; Jones, Rachel; Prenni, Jessica; Brinkley, Sarah Christine (2025)
This Mass Spectrometer Troubleshooting Guide is designed to support users in diagnosing and resolving common issues encountered during MS data acquisition. It includes four targeted flow charts that begin with specific problems users may observe: (1) empty chromatograms, (2) inaccurate mass values, (3) high signal in blank runs, and (4) instrument communication failure. Each flow chart provides a step-by-step diagnostic path, guiding the user to one of eight possible solutions. Solutions address common causes such as spray instability, method setup errors, system contamination, and calibration drift.